2017
DOI: 10.1589/jpts.30.2168
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prejudices and attitudes of students in the department of physical therapy against people with disabilities

Abstract: [Purpose] The purpose of this study is to examine prejudices and attitudes of students in the department of physical therapy, in order to suggest basic data for constructing an effective program to develop a positive attitude toward people with disabilities and lower social distance from them. [Subjects and Methods] For this study, students in the department of physical therapy participate in the survey examining prejudices and attitude towards people with disabilities. [Results] First, there were statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
(1 reference statement)
1
2
0
Order By: Relevance
“…No significant gender differences were found, similar to most recent studies [ 36 , 52 , 53 , 54 ], reinforcing the effect of this training to improve the global scores, which is independent from gender.…”
Section: Discussionsupporting
confidence: 89%
“…No significant gender differences were found, similar to most recent studies [ 36 , 52 , 53 , 54 ], reinforcing the effect of this training to improve the global scores, which is independent from gender.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of students felt that patients with disabilities faced difficulty in making friends and being accepted in society, but they were not a burden to society or their families. A study conducted among undergraduate students reported that those who have taken lectures are likely to feel like they can be friends with people with disabilities, work together, or spend time together [ 14 , 15 ]. A person with a disability may be discriminated against in society, and some people make fun of a person with a disability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was difference in the positive attitudes toward people with disabilities between students who have taken lectures of foundation of special education and those who have not. Students who have taken lectures are likely to feel being able to be friends with people with disabilities, to work together, or to spend time together 7 , 8 ) . In conclusion, it is necessary to provide disability awareness educational program including the theoretical knowledge and practical knowledge about the definitions, causes, characteristics, and educational strategy of all disabilities types for the university students in the department of physical therapy to reduce the overall prejudices against people with disabilities and increase positive attitudes of students toward people with disabilities.…”
Section: Discussionmentioning
confidence: 99%